Kingdom of Tonga : Early Childhood Development - World Bank (Washington, DC, 2014)
This report presents an analysis of the Early Childhood Development (ECD) programs and policies which affect young children in the Kingdom of Tonga. This report is part of a series of reports prepared by the World Bank using the Systems Approach for Better Education Results (SABER)-ECD framework and includes analysis of early learning, health, nutrition and social and child protection policies and interventions in the Kingdom of Tonga and regional and international comparisons. Tonga is a lower-middle-income country with a population of 104,509, of which approximately 13 percent are below the age of 5. SABER-ECD collects, analyzes and disseminates comprehensive information on ECD policies around the world. In each participating country, extensive multi-sectoral information is collected on ECD policies and programs through a desk review of available government documents, data and literature, and interviews with a range of ECD stakeholders, including government officials, service providers, civil society, development partners and scholars. The SABER-ECD framework presents a holistic and integrated assessment of how the overall policy environment in a country affects young children's development. SABER-ECD identifies three core policy goals that countries should address to ensure optimal ECD outcomes: establishing an enabling environment, implementing widely and monitoring and assuring quality. Improving ECD requires an integrated approach to address all three goals.